Usaha-Usaha Mahasiswa Dalam Memanfaatkan Waktu Luang Untuk Menambah Pendapatan Pada Mahasiswa Fakultas Keguruan Dan Ilmu Pendidikan Universitas Syiah Kuala - Khairun Nisak; Musfiana Musfiana; Irsyadillah Irsyadillah (Jurnal Ilmiah Mahasiswa Pendidikan Ekonomi, 2019)
This study entitled "Student Efforts in Utilizing Spare Time To Increase Revenue At Students Faculty of Teacher Training and Education University of Syiah Kuala". This research raises about the efforts undertaken by students in the use of leisure time. The purpose of this study is to find out what are the efforts of students in utilizing spare time to increase income on FKIP Unsyiah students. The subject of this research is all students of FKIP Unsyiah who do business as many as 18 students, the object of this research is student effort in utilizing spare time to increase the income of FKIP Unsyiah students. The type of research used is descriptive research with qualitative approach. Data collection techniques in this research is library research and field research in the form of observation and interview. Data processing techniques in this study presents all research results obtained into the paper. From the result of data analysis, it can be concluded that the student's effort in using spare time to increase the income of FKIP Unsyiah students is the effort of sewing, distro, olshop, selling package card and pulse, makeup, making cake, bucket flower, brown bucket and photo wood. In doing this research many have limitation that is limitation of energy, time, and cost. Therefore the researcher is looking forward to constructive suggestions.